25-6x=5-8x

Simple and best practice solution for 25-6x=5-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25-6x=5-8x equation:


Simplifying
25 + -6x = 5 + -8x

Solving
25 + -6x = 5 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
25 + -6x + 8x = 5 + -8x + 8x

Combine like terms: -6x + 8x = 2x
25 + 2x = 5 + -8x + 8x

Combine like terms: -8x + 8x = 0
25 + 2x = 5 + 0
25 + 2x = 5

Add '-25' to each side of the equation.
25 + -25 + 2x = 5 + -25

Combine like terms: 25 + -25 = 0
0 + 2x = 5 + -25
2x = 5 + -25

Combine like terms: 5 + -25 = -20
2x = -20

Divide each side by '2'.
x = -10

Simplifying
x = -10

See similar equations:

| -7/8*16 | | X/5-6=-10 | | 13=6x-3-5x | | -7/8x16 | | E^x^1/6 | | 6(y+5)=9y+9 | | 5x-22=2-7x | | -6(6x-1)=-174 | | (2x^5)(-2x^8)(3x^6)= | | 2(z-1)=5(z+8)-15 | | (5u+4)(9-u)=0 | | -3(1x+2)=-21 | | 7x^2-40x=2x^2-5x | | 59=6x+x+10 | | (11x+3)+(6x-5)= | | 3*5xytu=5 | | 3xy=8x | | n^2+n=4n | | (12x^2+6x-6)-(12x^2+9x+3)= | | -4s+6t=5 | | -x+6+4x=-21 | | xyz=27 | | 70-10(4x+6)=40 | | ghj=9 | | 10000000000=2x | | -2x^2-22=0 | | 4-21=9x-5-8x | | (8+u)(5u+1)=0 | | 165.832=10.91 | | 0.500=(x+12.00/2)3.60 | | 55+2x+x-10=180 | | 5(4x+2)=15 |

Equations solver categories